Video partitioning by temporal slice coherency - NGO, Chong-wah (Institutional Knowledge at Singapore Management University, 2001)
We present a novel approach for video partitioning by detecting three essential types of camera breaks, namely cuts, wipes, and dissolves. The approach is based on the analysis of temporal slices which are extracted from the video by slicing through the sequence of video frames and collecting temporal signatures. Each of these slices contains both spatial and temporal information from which coherent regions are indicative of uninterrupted video partitions separated by camera breaks. Properties could further be extracted from the slice for both the detection and classification of camera breaks. For example, cut and wipes are detected by color-texture properties, while dissolves are detected by statistical characteristics. The approach has been tested by extensive experiments.